Perbandingan Hukum Pidana Tentang Kejahatan Kekerasan Seksual di Indonesia dan Singapura - Sigit Kamseno; Agam Sakti Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study discusses the comparison of criminal law related to sexual violence in Indonesia and Singapore, focusing on the legal framework, definition and types of sexual violence, law enforcement process, and sanctions and punishments. In Indonesia, criminal law on sexual violence is regulated through Law No. 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS) and the Criminal Code (KUHP), which covers various forms of sexual violence. Singapore uses the Penal Code and the Women's Charter as the legal basis, with additional protection for children through the Children and Young Persons Act (CYPA). This study found that Indonesia has a broader and more comprehensive definition of sexual violence than Singapore, which tends to be more specific. The law enforcement process in both countries involves reporting, investigation by the police, and the courts, but Singapore has a special unit that handles sexual crimes with a more focused focus. Sanctions and punishments in Singapore tend to be heavier, including caning, while in Indonesia, punishments vary depending on the type of sexual violence. The research method applied in this study is the normative legal method, which focuses on the analysis of laws and regulations, legal documents, and legal concepts relevant to a legal problem. The approach used is a conceptual approach, which prioritizes analysis from a problem-solving perspective. This approach involves understanding the legal concepts that underlie or form the background of the problem, as well as considering the values ​​contained in the normative of a regulation related to these concepts.